2011
DOI: 10.1088/0031-9155/56/22/013
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic image quality of rotating slat versus parallel hole-collimated SPECT

Abstract: Abstract. Parallel and converging hole collimators are most frequently used in nuclear medicine. Less common is the use of rotating slat collimators for Single Photon Emission Computed Tomography (SPECT). The higher photon collection efficiency, inherent to the geometry of rotating slat collimators results in much lower noise in the data. However, plane integrals contain spatial information in only one direction, whereas line integrals provide two-dimensional information. It is not a trivial question whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
2
1
Order By: Relevance
“…However, in volume imaging, the gain of using the RS collimator in our study is very different from that proposed in [12], where it was found that the RS collimator is 2-3 times better than the PH in hot spot imaging, and more than 4 times better in cold spot imaging. One of the main reasons is that the collimator apertures in [11], [12] were the same for both collimators, whereas in our study we applied the optimal collimator aperture for each system to ensure a fair comparison. The discrepancy could also be partially explained by the influence of photon scatter, which was modelled in [12] but not in this paper.…”
Section: Optimal Aperturecontrasting
confidence: 99%
See 2 more Smart Citations
“…However, in volume imaging, the gain of using the RS collimator in our study is very different from that proposed in [12], where it was found that the RS collimator is 2-3 times better than the PH in hot spot imaging, and more than 4 times better in cold spot imaging. One of the main reasons is that the collimator apertures in [11], [12] were the same for both collimators, whereas in our study we applied the optimal collimator aperture for each system to ensure a fair comparison. The discrepancy could also be partially explained by the influence of photon scatter, which was modelled in [12] but not in this paper.…”
Section: Optimal Aperturecontrasting
confidence: 99%
“…One of the main reasons is that the collimator apertures in [11], [12] were the same for both collimators, whereas in our study we applied the optimal collimator aperture for each system to ensure a fair comparison. The discrepancy could also be partially explained by the influence of photon scatter, which was modelled in [12] but not in this paper. The dimensions of the phantom used in this study were relatively small compared to the human size.…”
Section: Optimal Aperturementioning
confidence: 99%
See 1 more Smart Citation